SISTEM PENDIDIKAN DI NEGARA PERANCIS - Abdul Wahab Syakhrani; Juhratun Juhratun; Nikmah Nikmah; Mukarramah Mukarramah; Nor Hayati (ADIBA : JOURNAL OF EDUCATION, 2022)
The education system in France uses a centralized system, namely education that is fully centered on the government. So, the ministry of education (commonly called the Ministry of National Education) has an urgent role in the progress of education as a whole. In addition, the government also emphasizes the existence of a 16-year compulsory education system with the implementation of a free school system for every level of education. Students are directly directed to talents and interests and to conceptual understanding, students are accustomed to learning with a hard pattern, discipline and filled with assignments. After students take compulsory education. Children receive pre-school primary education at the age of two to six years, elementary school between seven and 10 years and junior high (Collège)-SMA (Lycées) between 11 and 18 years of age, while higher education is for those over 19 years of age.